LncRNA DQ786243 contributes to proliferation and metastasis of colorectal cancer both in vitro and in vivo. Issue 3 (6th May 2016) - Sun, Longci; Xue, Hanbing; Jiang, Chunhui; Zhou, Hong; Gu, Lei; Liu, Ye; Xu, Chunjie; Xu, Qing
Abstract : This article aims to find the key long non-coding RNAs (LncRNAs) associated with colorectal cancer (CRC) and to study its biological functions in colorectal cancer progression. Our study has shown that upregulated LncRNA DQ786243 can regulate cell proliferation, cell cycle progression, cell apoptosis, migration, and invasion in CRC cells. Xenograft experiments confirmed that the growth of xenograft tumors formed by CRC cells was suppressed after silencing LncRNA DQ786243 expression. In conclusion, our study suggests that LncRNA DQ786243 is an oncogene that promotes tumor progression and leads us to propose that LncRNAs may serve as key regulatory hubs in CRC progression. Abstract : Accumulating evidence demonstrates that long non-coding RNAs (LncRNAs) play important roles in regulating gene expression and are involved in various cancers, including colorectal cancer (CRC). However, LncRNA profiles in CRC remain largely unknown. The present study aims to find the key LncRNA associated with CRC and to study its biological functions in CRC progression. We focused on LncRNA DQ786243, one of LncRNAs which promoted development of CRC from the Gene Expression Omnibus (GEO) and validated using quantitative real-time PCR among about 20 paired CRC tissues. The effects of LncRNA DQ786243 were assessed by silencing the LncRNA in vitro and in vivo . Results showed that the expression level LncRNA DQ786243 was significantly higher in CRC tissues and cell lines. We also found LncRNA DQ786243 knockdown by RNA interference with siRNA significantly arrested the cell cycle in the G2 /M-phase, promoted apoptosis and weaken the abilities of cell proliferation and invasion in vitro . Further investigation into the mechanisms responsible for the growth inhibitory effects by DQ786243 silencing revealed that its knockdown resulted in the induction of cell cycle arrest and apoptosis through certain cell cycle-related and apoptosis-related proteins. Finally, xenograft experiments confirmed that the growth of xenograft tumours formed by CRC cells was suppressed after silencing LncRNA DQ786243 expression. In conclusion, the present study suggests that LncRNA DQ786243 is an oncogene that promotes tumour progression and leads us to propose that LncRNAs may serve as key regulatory hubs in CRC progression.